Primary school learners with characteristics of dyslexia: auto-ethnographic approach to the effectiveness of the screening, identification, assessment, and support policy in South Africa - Kgatse, Karabo Moses; Khanare, Fumane; Adewuyi, Habeeb Omoponle (Frontiers in Education, 2024)
The implementation of the Screening Identification Assessment and Support (SIAS) policy has been ongoing for almost a decade to provide care and support to all learners, including those with neurodevelopmental challenges such as dyslexia. Despite these efforts, many primary school learners continue to experience barriers to learning associated with dyslexia. This phenomenon is of great concern in rural communities where dyslexia is generally ignored and misunderstood. On the other hand, there is a lack of research investigating the effectiveness of the SIAS policy in supporting learners with dyslexia. Existing studies often focus on dyslexia and the SIAS policy in isolation. The 'qualitative research' approach was adopted. Autoethnography was employed as the study's design, positioned within the interpretivism paradigm to investigate the effectiveness of the SIAS policy in supporting learners with dyslexia characteristics in Tlokweng village. The sample consists of (5) participants and Critical reflection and auto-interviewing methods were used to generate data, which was thematically analysed. Bronfenbrenner's Ecological Systems Theory was used to understand the interaction between learners, their environment, and the SIAS policy. The findings suggest that the SIAS policy is ineffective in its screening process. Also, learners' perceptions indicate a gap in teachers' readiness to address learning barriers associated with the characteristics of dyslexia. Lastly, there is a need for continuous monitoring of the SIAS implementation.